2011 IEEE 11th International Conference on Data Mining Workshops 2011
DOI: 10.1109/icdmw.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Time-Aware Ranking in Dynamic Citation Networks

Abstract: Abstract-Many algorithms have been developed to identify important nodes in a complex network, including various centrality metrics and PageRank, but most fail to consider the dynamic nature of the network. They therefore suffer from recency bias and fail to recognize important new nodes that have not had as much time to accumulate links as their older counterparts. This paper describes the Effective Contagion Matrix (ECM), a solution to address recency bias in the analysis of dynamic complex networks. The ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
(37 reference statements)
0
35
0
10
Order By: Relevance
“…The tool returns for a given article the identifiers (pmids/pmcids) of all articles that cite, or are cited by it. Two citation-based impact measures are calculated on the constructed network: the PageRank [5] and the RAM scores [6]. These two measures were selected based on the results of a recent experimental study [7], which found them to perform best in capturing the overall and the current impact of an article (i.e., its "influence" and its "popularity"), respectively .…”
Section: Calculation Of Citation-based Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The tool returns for a given article the identifiers (pmids/pmcids) of all articles that cite, or are cited by it. Two citation-based impact measures are calculated on the constructed network: the PageRank [5] and the RAM scores [6]. These two measures were selected based on the results of a recent experimental study [7], which found them to perform best in capturing the overall and the current impact of an article (i.e., its "influence" and its "popularity"), respectively .…”
Section: Calculation Of Citation-based Measuresmentioning
confidence: 99%
“…The same holds for the tweet counting process 7 . For the calculation of popularity (RAM [6]) and influence (PageRank [5]) scores, the open PaperRanking [7] library 8 was used. Finally, retrieving Twitter objects based on given tweet IDs was done using the twarc Python library 9 .…”
Section: Code Availabilitymentioning
confidence: 99%
“…To assess the importance of papers, graph ranking algorithms such as PageRank and its variants have been applied [10,20,21,22]. In [10], the authors further take time into consideration in order to overcome the recency bias that favors "old" papers. Apart from this, graph clustering is investigated to identify meaningful topics, such as [5,8,18,19].…”
Section: Related Workmentioning
confidence: 99%
“…Even sophisticated citation-based measurement, e.g., [10,20,21,22], without taking into account of topics, can lead to bad judgement: a well recognized theoretic paper about graphic model in "Bayes learning" might receive less credit in "data engineering" and "very large database" due to the computational difficulty that limits its application.…”
Section: Topic Milestone Papersmentioning
confidence: 99%
“…Beyond simple citations count, researchers have explored methods that analyze the structure of citation networks to identify important papers [31], [32] or predict which papers will be important in the future [33].…”
Section: Related Workmentioning
confidence: 99%